2018
DOI: 10.1093/jn/nxx043
|View full text |Cite
|
Sign up to set email alerts
|

Cow Milk Consumption Increases Iodine Status in Women of Childbearing Age in a Randomized Controlled Trial

Abstract: The present study shows that the consumption of additional cow milk can significantly increase UIC in women of childbearing age. These results suggest that cow milk is a potentially important dietary source of iodine in this population group. This trial was registered at www.clinicaltrials.gov as NCT02767167.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
9
2
Order By: Relevance
“…Consideration should also be given to expanded public health schemes to provide milk and iodine‐containing supplements to women contemplating pregnancy, pregnant and nursing women. One recent randomised controlled study of free milk provision in non‐pregnant women demonstrated a doubling of intake from <140 mL/day and an improvement in mUIC from a deficient range to a sufficient range after three months 70 …”
Section: Resultsmentioning
confidence: 99%
“…Consideration should also be given to expanded public health schemes to provide milk and iodine‐containing supplements to women contemplating pregnancy, pregnant and nursing women. One recent randomised controlled study of free milk provision in non‐pregnant women demonstrated a doubling of intake from <140 mL/day and an improvement in mUIC from a deficient range to a sufficient range after three months 70 …”
Section: Resultsmentioning
confidence: 99%
“…Normal serum iodine in control group and pregnant groups may be due to iodine enriched table salt distributed in Iraq during last ten years in an affordable price. O'Kane SM et al found that cow milk consumption increases iodine status in women of childbearing age [10] . We may need further assessment of thyroid gland function and size among Iraqi pregnant women in future studies as iodine is important for the production of thyroid hormones that affect many metabolic processes like maturation of central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the elderly population above 55 years, hyperthyroidism (excess production of thyroid hormone) is most common [45,46]. Adult deficiency could be related to decreased milk consumption [47]. It is probable that adults may show greater chances of developing iodine deficiency when compared to the younger population due to their lower milk consumption [48].…”
Section: Adulthood and The Elderlymentioning
confidence: 99%